Impact of international court of justice decisions on Batu Puteh, Middle Rocks and South Ledge towards Malaysia maritime boundary [electronic resource] - Khairul Amri Ramlee, 1990- 633986; Mohd. Razali Mahmud, 1961- 544288; Fakulti Geoinformasi dan Harta Tanah 555724 (2013)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik)) - Universiti Teknologi Malaysia, 2013